Innovative gamification strategies to improve student learning outcomes in vocational high schools - Faza, Muhammad Iqbal; Iskandar, Ranu; Naryanto, Rizqi Fitri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The purpose of this research is to develop gamification-based learning media operated through the Android platform and test its effectiveness on student learning outcomes. The research method used is the ADDIE model, which involves five stages: Analysis, Design, Development, Implementation, and Evaluation. This means that researchers conduct analysis, researchers make designs for learning media so that students are not bored while learning, researchers develop media that are more interesting than previous research, researchers implement by making learning media, and evaluate to develop further research. Validation of this gamification learning media was carried out by linguists, material experts, and media experts. The trial was conducted on students of class XI TKR 1 and 2 at Mataram Semarang Vocational High School, with a total of 61 students. The data analysis of this research was conducted using a t-test. The results of this study showed that: (1) The validation results from linguists amounted to 95%, material experts amounted to 90.5%, and media experts amounted to 87.2%, meaning that the gamification learning media developed proved to be very feasible to use in learning so that students are not saturated and bored. (2) The average pre-test score was 65.44, and after learning using the gamification application, the average score was 79.56, with an increase of 14.12, and the t-test results showed a p-value of 0.00 <0.05, which means that gamification learning media has a significant impact on improving learning outcomes and increasing student interest in learning. (3) The use of gamification learning media as learning media is very good for students, as it allows students to be more independent in learning and not only rely on explanations from teachers.